PROBLEMS AND NECESSITIES OF INFORMING OF POPULATION OF TERRITORIES, MUDDY RADIO-ACTIVE MATTERS - I. V. Kochin; O. M. Akulova; P. I. Sidorenko; V. M. Vasilenko; O. O. Gajvolya (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Humanity more critically and responsibly estimates possibilities to control the risks of consequences of human activity. More attention is spent for the spare of notification system about failures on AES and questions of informing population about radiation contamination. The experts of Worldwide nature protection organization of Greenpeace consider that in case of scale failure on AES population presently is badly protected from radiation influencing, as well as before, people are not enough informed about its consequences.